Wired for insight—recent advances in Caenorhabditis elegans neural circuits. (August 2021) - Byrd, Dana T.; Jin, Yishi
Abstract: The completion of Caenorhabditis elegans connectomics four decades ago has long guided mechanistic investigation of neuronal circuits. Recent technological advances in microscopy and computation programs have aided re-examination of this connectomics, expanding our knowledge by both uncovering previously unreported synaptic connections and also generating models for neural networks underlying behaviors. Combining molecular information from single cell transcriptomes with elegant tools for cell-specific manipulation has further enhanced the ability to precisely investigate individual neurons in behaving animals. This mini-review aims to provide an overview of new information on connectomics and progress toward a molecular atlas of C. elegans nervous system, and discuss emerging findings on neuronal circuits.